РОЛЬ СЕЛЬСКОГО ХОЗЯЙСТВА В ЭКОНОМИКЕ НАШЕЙ СТРАНЫ (Журнал «Маркетинг», 2025)
В статье освещается роль сельского хозяйства Республики Узбекистан в экономике страны. Раскрыта доля сельского хозяйства в ВВП и его значение в обеспечении занятости населения. Отмечено, что отрасль сталкивается с рядом сложных проблем, требующих решения.
Keywords: сельское хозяйство; агробизнес; крестьянское хозяйство; агропромышленный комплекс. Agriculture has always been the backbone of our countryʼs economy; playing a vital role in shaping its development and progress. Despite rapid industrialization and technological advancement; agriculture remains a key sector for economic stability; employm ent; and food security. Agriculture is the largest sector of the Republic of Uzbekistanʼs economy. Agriculture primarily serves to meet the populationʼs food needs. In this regard; Uzbekistanʼs agriculture has achieved tremendous success. The country produces almost the majority of agricultural food products; in sufficient quantities for its population. Agriculture provides the processing industry with raw materials. Today; over 60% of the fiber used in the countryʼs light and textile industries is domestically produced cotton fib er. The rest is wool; hemp; cocoons; and chemical fibers. The republicʼs fruit; vegetable; and melon processing industry relies entirely on locally grown raw materials. The dairy and meat processing industries also rely on № 10-SON OKTA BR; 2025 -YIL 67 locally grown produce. Raw materials for the oil and fat industry are primarily grown domestically. Only a few types of vegetable oil are produced from imported raw materials. For example; the quality of the oils consumed by the countryʼs residents — the qua lity of which ensures a wide variety —casts a shadow. Of course; this represents a very small portion of all the oils and butter produced. The success of the countryʼs economic and social reforms depends largely on the level of agricultural development. Since agriculture is a sector of political; economic; and social importance for our country; it performs the following functions (Table 1): Table 1. The functions of agriculture in our country1 forms the food fund of our country supplies gomash for the agricultural processing industry; ensures food independence and security of our country provides jobs to the population. As a result of reforms implemented during the years of independence; the Republic of Uzbekistan has acquired a dynamically developing and complex economic system. Agriculture has remained a large and important sector of the Republicʼs economy. Agriculture is one of the main industries practiced by the peoples of Uzbekistan since ancient times; and has been steadily developing for several millennia. Livestock farming is the primary industry in the republic; with an agricultural culture developing later. Shee p farming; cattle breeding; horse breeding; beekeeping; camel breeding; sericulture; grain farming; vegetable growing; melon growing; horticulture; and cotton growing are predominantly developed. Agriculture has become the main way of life for the peoples living in our republic. Its development has led to an increase in the production of agricultural tools in our country. As a result; culture; science; and crafts have gradually developed. Table 2 The role of the republicʼs agriculture in the countryʼs economy2 № Indicators 2017 2018 2019 2020 2021 2022 1 The share of agricultural GDP in the countryʼs GDP; % 28; 9 26; 6 24; 4 24; 9 24; 6 23; 5 2 Growth rate of gross agricultural output; % 103; 2 104; 5 106; 1 107; 3 110; 1 106; 2 3 weight of cotton fiber and food products in gross exports; % 22; 9 15; 9 9; 9 8; 5 7; 9 7; 0 4 Agricultural labor force share; % 27; 2 26; 6 26; 4 25; 2 24; 9 Today; agriculture plays a significant role in the countryʼs economy. This sector accounts for 20 -25% of the countryʼs gross domestic product. In 2021; it accounted for 24.6% of the countryʼs total GDP; compared to 23.5% in 2022. More than half of the 1 Central Asian journal of education and innovation; Volume2; Issue 5 2 https:// stat.uz № 10-SON OKTA BR; 2025 -YIL 68 free foreign exchange earnings needed for our economy come from exports of this sectorʼs products. Specifically; in 2022; the share of cotton and food products in total exports was 7.0%. More than 96 percent of food grown in the country is produced in agriculture. More than 60% of the population lives in rural areas. Our peopleʼs standard of living and the employment of a significant portion of the human resource are linked to agriculture. Today; more than 28% of the labor force employed in the economy is employed in agriculture and forestry. Therefore; the focus on agriculture; especially in the years following independence; is rightfully increasing (Table 2). As Table 2 shows; agriculture is the largest sector of the Republic of Uzbekistanʼs economy; and its share is declining year after year. It should be noted that; from 2017 to 2022; agriculture experienced steady growth. Thanks to the relatively rapid development of industry and the service sector; agricultureʼs share in the countryʼs economy has decreased. This is considered a very positive development. As the countryʼs economy accelerates; agricultureʼs share will decrease. As a result; we will become a developed industrialized country with a well - developed service sector. The republicʼs foreign trade turnover in 2023 was $62.6 billion; of which exports amounted to $24.4 billion; while exports of agricultural and food products accounted for nearly $2 billion; or 8.2% of the total (Table 3). Table 3. Countries with the highest share in the foreign trade turnover of the Republic of Uzbekistan(2023 y)1 Country / Partner TSA (million USD) Export (million USD) Import (million USD) Share (%) China (PRC) 13; 722.0 2; 461.8 11; 260.1 21.9% Russia 9; 883.8 3; 307.6 6; 576.1 15.8% Kazakhstan 4; 398.9 1; 372.5 3; 026.4 7.0% Turkiye 3; 099.7 1; 248.5 1; 851.2 5.0% Republic of Korea 2